Good news is bad news: Leverage cycles and sudden stops - Ozge Akinci; Ryan Chahrour (Federal Reserve Bank of New York, 2015)
We show that a model with imperfectly forecastable changes in future productivity and an occasionally binding collateral constraint can match a set of stylized facts about "sudden stop" events. "Good" news about future productivity raises leverage during times of expansion, increasing the probability that the constraint binds, and a sudden stop occurs, in future periods. The economy exhibits a boom period in the run-up to the sudden stop, with output, consumption, and investment all above trend, consistent with the data. During the sudden stop, the nonlinear effects of the constraint induce output, consumption, and investment to fall substantially below trend, as they do in the data.
Keywords: E32; F41; F44; G15; 330; news shocks; sudden stops; leverage; boom-bust cycle